Common Polymorphisms in the CD43 Gene Region Are Associated With Tuberculosis Disease and Mortality. - Campo, M; Randhawa, A; Randhawa, A; Dunstan, S; Dunstan, S; Farrar, J; Farrar, J; Caws, M; Caws, M; Bang, N; Bang, N; Lan, N; et al. (2014)
CD43, a surface glycoprotein, regulates Mycobacterium Tuberculosis macrophage binding, replication and pro-inflammatory cytokine induction in a murine model. We hypothesized that single-nucleotide polymorphisms (SNPs) in the CD43 gene region are associated with human tuberculosis (TB) susceptibility. We performed a case-population study in discovery (352 TB cases and 382 controls) and validation cohorts (339 TB cases and and 376 controls). We examined whether 11 haplotype-tagging SNPs in the CD43 gene region were associated with tuberculous meningitis (TBM) and pulmonary (PTB) tuberculosis in Vietnam. Three SNPs from the CD43 gene region were associated with tuberculosis susceptibility with a genotypic model. The association fit a recessive genetic model and was greater for TBM than PTB (for TBM: rs4788172 (OR 1.64, 95% CI 1.04, 2.59), rs17842268 (OR 2.20, 95% CI 1.29, 3.76), and rs12596308 (OR 2.38, 95% CI 1.47, 3.89). Among TBM cases, rs17842268 was associated with decreased survival (HR=2.7; CI 95% 1.1-6.5; p=0.011). In addition, rs12596308 and rs17842268 were associated with focal neurologic deficit at TBM presentation. Our data suggests that CD43 polymorphisms are associated with tuberculosis susceptibility, disease manifestations, and worse outcomes. To our knowledge this is the first report that links CD43 genetic variants with susceptibility and outcome from a disease.